Effect of Diet Containing Gracilaria Sp. Waste and Multi-Enzyme Additives on Blood Lipid Profile of Local Duck - Frasiska, Nurul; Suprijatna, Edjeng; Susanti, Siti (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2016)
This study was aimed to evaluate the effect of diet containing waste of seaweed Gracilaria sp. on local duck blood lipid profiles including cholesterol, triglycerides, low density lipoprotein (LDL), and high density lipoprotein (HDL). The material in this study were 72 female Tegal ducks aged 22 weeks with 1,318 ± 121 gaverage body weight, diets containing Gracilaria sp. waste (GW) with 18% protein and 2900 kcal/kg metabolic energy and 150 g/ton feed commercial multi-enzyme (ME). Data were subject to Completely Randomized Design with 6 treatments, (T0) Basal Diets, (T0+) Basal Diets with ME, (T1) Diets with 10% GW, (T1+) Diets with 10% GW + ME, (T2+) Diets with 12.5 % GW + ME, and (T3+) Diets with 15% GW + ME. The treatment was givenfor 12 weeks and blood sample was taken onthe last week. The serum was separated and analyzed for blood lipid profiles using CHOD-PAP. Results showed that diet with 12.5%GW plus multi-enzyme additives significantly (P<0.05) affected blood lipid profiles of local duck, tended to lower triglycerides and LDL Cholesterol, but increase blood HDL levels.